Efektivitas Kombinasi Terapi Murottal Surah Ar-Rahman dan Aromaterapi Lemon terhadap Tingkat Nyeri Disminore - Nanda Elsa Prasetiyani; Apriliani Yuliani Wuriningsih (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Background: Dysmenorrhea is commonly experienced by female adolescents and may interfere with daily activities and academic concentration. Non-pharmacological interventions such as listening to the murottal of Surah Ar-Rahman and the use of lemon aromatherapy have been reported to provide relaxation and analgesic effects. However, evidence regarding the effectiveness of their combined use remains limited. Therefore, this study aimed to evaluate the effect of combined therapy using Murottal Surah Ar-Rahman and lemon aromatherapy on dysmenorrhea pain levels among female adolescents at SMA Negeri 10 Semarang. Method: This study was conducted at SMA Negeri 10 Semarang using a Quasi-Experimental design with a Pretest–Posttest Group approach. The population consisted of 188 students who met the inclusion criteria. The sample size was determined using the Slovin formula, resulting in 40 respondents selected through purposive sampling. A normality test was performed prior to analysis, and the bivariate analysis utilized the Wilcoxon Signed Rank Test. Result: The Wilcoxon Signed Rank Test showed a p-value of 0.000 (p < 0.05), indicating a significant difference between pain levels before and after the intervention. These findings demonstrate that the combination of Murottal Surah Ar-Rahman and lemon aromatherapy is effective in reducing dysmenorrhea pain among female adolescents at SMA Negeri 10 Semarang. Conclusion: The combined therapy of Murottal Surah Ar-Rahman and lemon aromatherapy is effective in reducing dysmenorrhea pain levels among female adolescents.